A New Shape Function for Simulating a Single Facial Wrinkle - Zainal Azmi, Nurazlin (2006)
Many efforts have been taken to generate realistic facial modeling and animation. This is inspired by the increasing appearance of virtual characters in film and video, inexpensive desktop processing power, and the potential for a new 3D immersive communication metaphor for human-computer interaction.